Class Discourse in Croatia: Where Did It Go? Is It Coming Back?. (August 2015) - Grdešić, Marko
This article summarizes recent trends in Croatia with regard to class analysis and class discourse. It traces the main currents both in academic debate as well as more broadly in the public sphere. Issues of class were sidelined with the outbreak of war and the rise of nationalism in the 1990s. Later, neoliberalism further weakened class and leftist discourse. Research on class has been sporadic and rare. New developments among a younger generation of leftist activists and scholars have begun to challenge the silence on class, but the main trends have not been reversed.